2016
DOI: 10.1121/1.4946987
|View full text |Cite
|
Sign up to set email alerts
|

Sound transmission loss of double plates with an air cavity between them in a rigid duct

Abstract: In this paper, the sound transmission loss (STL) of thin double plates with an air cavity between them in a rigid duct is considered using an analytical approach. The vibration motion of the plate and sound pressure field are expanded in terms of an infinite series of the modal functions. Under the plane wave condition, a low frequency solution is derived by including the first few symmetric modes. It is determined that the peak frequencies of the double plates coincide with those of each single plate. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Symbols with subscript 2 have the same meanings as defined above but applied to panel 2. e mn , b mn , c mn , d mn and A are amplitude constants related to the waves in the duct as shown in Figure 1. This is given by Kim et al [7]:…”
Section: ( B )mentioning
confidence: 99%
See 1 more Smart Citation
“…Symbols with subscript 2 have the same meanings as defined above but applied to panel 2. e mn , b mn , c mn , d mn and A are amplitude constants related to the waves in the duct as shown in Figure 1. This is given by Kim et al [7]:…”
Section: ( B )mentioning
confidence: 99%
“…The experiment samples were attached to a sample holder in the tube to provide a reliable boundary condition for each experiment. Firstly, the present model is compared with results of Kim et al [7] for plywood plate in Figure 3(a). The theoretical model for Kim et al for rectangular plate was modeled using the parameters given, and the present model agree well for all frequencies.…”
Section: ( B )mentioning
confidence: 99%
“…The results showed that the flexural vibration of a plate increased the acoustic absorption performance of the structure in water. In another work [299], the STL of a thin panel equipped with a cavity in a rigid duct was calculated. Herewith, the dynamic behavior and acoustic pressure were developed as an infinite series of modal functions.…”
Section: Theorymentioning
confidence: 99%
“…The motion of the panels was modeled in space-harmonic expansion as described by Mead and Pujara. 7 It should be noted that several authors have reported the limitations of double-wall structures at low frequency in the region of mass air mass resonance, at which the model for infinite panels delineate an out-ofphase motion 2,8,9 Thus, numerous methods are being investigated to enhance double walls for better STL. One of such methods adopted is the filling of the cavity of the double wall with filler materials.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that several authors have reported the limitations of double-wall structures at low frequency in the region of mass air mass resonance, at which the model for infinite panels delineate an out-of-phase motion 2,8,9…”
Section: Introductionmentioning
confidence: 99%